BIBLICAL PERSPECTIVES ON CARDIOVASCULAR HEALTH MAINTENANCE: INTEGRATING SPIRITUAL STEWARDSHIP WITH PREVENTIVE CARDIOLOGY AND HOLISTIC NURSING - Langingi, Nova Lina; Kaparang, Grace Fresania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cardiovascular disease (CVD) remains the leading cause of mortality worldwide despite significant advances in treatment and prevention strategies. Lifestyle modification is recognized as the cornerstone of cardiovascular prevention. Increasingly, healthcare scholars acknowledge the importance of integrating spiritual and holistic dimensions into health promotion. Biblical teachings contain principles related to diet, self-control, rest, emotional peace, and stewardship of the body that conceptually align with evidence-based cardiovascular prevention strategies. This study aimed to analyze cardiovascular health maintenance from biblical perspectives and integrate scriptural principles with contemporary preventive cardiology concepts. A qualitative descriptive theological analysis design was employed. Primary data sources included selected biblical scriptures from the Old and New Testaments, while secondary sources consisted of contemporary literature related to cardiovascular prevention, lifestyle medicine, spirituality, and holistic nursing. Data were analyzed using thematic analysis to identify relationships between biblical teachings and cardiovascular health behaviors. Five major themes emerged: (1) stewardship of the body, (2) plant-based dietary principles, (3) temperance and self-control, (4) Sabbath rest and physiological restoration, and (5) emotional peace and stress regulation. These themes demonstrated conceptual alignment with evidence-based cardiovascular prevention approaches including healthy dietary patterns, stress reduction, metabolic regulation, and behavioral lifestyle modification. Biblical perspectives provide a holistic conceptual framework for cardiovascular health maintenance that complements preventive cardiology and holistic nursing practice. Integrating spiritual principles into cardiovascular health promotion may strengthen patient-centered and faith-sensitive healthcare interventions.